PENERAPAN ALGORITMA KLASIFIKASI DATA MINING DALAM PENENTUAN PEMBERIAN PINJAMAN KOPERASI - Nandang Iriadi (LPPM Universitas Bina Sarana Informatika, 2012)
The loan is the delivery of goods, services, or money from one party (the creditor / lender) on thebasis of trust in the other party (customer or debtor / borrower) to the appointment of a receiver topay credit to the lender on the date agreed upon by both parties. Research each loan application ishighly dependent on factors such as type of business, the economy, the intended use of the credit,the amount of credit that do not kredit.Analisa carefully and thoroughly resulted in someborrowers who have no credit given the ability to make payments so that there was nonperforming loans. In this study, using the method of C4.5 algorithm, which was applied to the data members Multipurpose Cooperative Enterprises